The Discrusive Power of Verbal Violence in Indonesian Social Media: A Linguistic Corpus Study - Dewanty, Imanuella Anastasia Brigitha Carneliaputri; Saryono, Djoko; Zahro, Azizatus; Razak, Zainur Rijal Abdul; Ismail, Habibah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
The rise of gender-based, political, and identity-based verbal violence on social media highlights the urgency of understanding how language plays a role in the reproduction of power in digital culture. This study aims to analyze the linguistic and ideological structures that shape practices of verbal violence in digital interactions. Data were collected from July 2024 to January 2025 from various social media platforms, then analyzed using corpus linguistics to identify patterns of language use, as well as Fairclough's Critical Discourse Analysis to interpret the power relations that emerge in the texts. The results show that digital verbal violence is not merely an expression of individual emotion, but is connected to dominant ideologies such as patriarchy, toxic nationalism, and religious fanaticism. Violent speech contains both vertical and horizontal power relations, which allow users to assert symbolic authority, silence others, or negotiate certain identities. These findings confirm that verbal violence in digital spaces is not merely a matter of communication ethics, but part of the mechanism of power reproduction through linguistic practices. In conclusion, this study contributes to understanding how language in social media reproduces power and ideology in digital interactions. As a follow-up, future research may expand the data scope or examine counter-discursive strategies to challenge verbal violence online. The findings have implications for critical digital literacy by helping users recognize and resist ideological domination embedded in everyday social media discourse.